АКУМУЛЮЮЧІ ПРИСТРОЇ ДЛЯ СИСТЕМ АВТОНОМНОГО ЖИВЛЕННЯ СВІТЛОТЕХНІЧНИХ УСТАНОВОК - Андрійчук, В.А.; Філюк , Я.О. (Інститут електродинаміки НАН України, Київ, 2017)
The article presents findings for electrical parameters of supercapacitors, and techniques for experimental definition of capacitance values and internal resistance of supercapacitors. Research on self-discharge and influence of delay within electric field upon self-discharge constant of supercapacitors has been conducted. Monitoring system for supercapacitors and Li-ion battery charge/discharge based on the verifier with pulse-width modulation and voltage balancing system which is employed on a separate battery element has been proposed. References 19, tables 2, figures 8.